Multiple but Asymmetric Bank Financing: The Case of Relationship Lending - Ralf Elsas; Frank Heinemann; Marcel Tyrell (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2004)
Empirical evidence suggests that even those firms presumably most in need of monitoring-intensive financing (young, small, and innovative firms) have a multitude of bank lenders, where one may be special in the sense of relationship lending. However, theory does not tell us a lot about the economic rationale for relationship lending in the context of multiple bank financing. To fill this gap, we analyze the optimal debt structure in a model that allows for multiple but asymmetric bank financing. The optimal debt structure balances the risk of lender coordination failure from multiple lending and the bargaining power of a pivotal relationship bank. We show that firms with low expected cash-flows or low interim liquidation values of assets prefer asymmetric financing, while firms with high expected cash-flow or high interim liquidation values of assets tend to finance without a relationship bank.
Keywords: G33; G78; G21; 330; relationship lending; multiple bank financing; lender coordination; Fremdkapital; Kredit; Bank; Finanzierung; Lieferanten-Kunden-Beziehung; Theorie